Nutraceutical Supplementation Ameliorates Visual Function, Retinal Degeneration, and Redox Status in rd10 Mice - Lorena Olivares-González; Sheyla Velasco; Isabel Campillo; David Salom; Emilio González-García; José Miguel Soriano del Castillo; Regina Rodrigo (MDPI AG, 2021)
Retinitis pigmentosa (RP) is a group of inherited retinal dystrophies characterized by progressive degeneration of photoreceptor cells. Ocular redox status is altered in RP suggesting oxidative stress could contribute to their progression. In this study, we investigated the effect of a mixture of nutraceuticals with antioxidant properties (NUT) on retinal degeneration in rd10 mice, a model of RP. NUT was orally administered to rd10 mice from postnatal day (PD) 9 to PD18. At PD18 retinal function and morphology were examined by electroretinography (ERG) and histology including TUNEL assay, immunolabeling of microglia, Müller cells, and poly ADP ribose polymers. Retinal redox status was determined by measuring the activity of antioxidant enzymes and some oxidative stress markers. Gene expression of the cytokines IL-6, TNFα, and IL-1β was assessed by real-time PCR. NUT treatment delayed the loss of photoreceptors in rd10 mice partially preserving their electrical responses to light stimuli. Moreover, it ameliorated redox status and reduced inflammation including microglia activation, upregulation of cytokines, reactive gliosis, and PARP overactivation. NUT ameliorated retinal functionality and morphology at early stages of RP in rd10 mice. This formulation could be useful as a neuroprotective approach for patients with RP in the future.